Flat square ceiling with a large lotus medallion - Temples of India Project Team (Jio Institute, 2024)
This is the flat square ceiling in the aisles of the mandapa (pillared hall). The ceiling is made up of a large lotus medallion, surrounded by floral patterns. The beams below the flat ceiling have friezes with various human figures.